2007
DOI: 10.1079/pavsnnr20072034
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathy for weed management in sustainable agriculture.

Abstract: The sustainability of agriculture relies on the development of strategies that lower the need for costly external inputs and minimize detrimental effects on the environment, which often involve either inappropriate or excessive use of agrochemical inputs. One strategy, integrating plant allelopathy into sustainable agriculture, is discussed in this paper. Agriculture integrated with allelopathy could reduce the heavy dependence on synthetic herbicides and other agrochemicals, and therefore ease problems such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 146 publications
0
9
0
Order By: Relevance
“…Much effort has been made to control weeds by exploiting the allelopathy of rice over the last four decades [ 9 ]. More than 16,000 rice varieties collected from 99 countries have been evaluated for their allelopathic potential, and revealed that ≈4.0% of rice cultivars show weed-suppression of paddy weeds [ 4 , 25 ]. Some reports have shown that Japonica rice cultivars have higher allelopathic potential than Indica rice varieties [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much effort has been made to control weeds by exploiting the allelopathy of rice over the last four decades [ 9 ]. More than 16,000 rice varieties collected from 99 countries have been evaluated for their allelopathic potential, and revealed that ≈4.0% of rice cultivars show weed-suppression of paddy weeds [ 4 , 25 ]. Some reports have shown that Japonica rice cultivars have higher allelopathic potential than Indica rice varieties [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous allelochemicals derived from plants have been described to stimulate and/or inhibit other species’ germination and growth. Intense scientific efforts have focused in the past on describing the mechanisms used by plants to self-regulate their own and other species’ densities and distribution or those found at the basis of biological invasions via allelopathic interactions [ 4 , 5 ]. Allelopathic crop varieties can release their own “phytotoxins” as allelochemicals to reduce the growth of weeds, thus permitting ecological weed management in cropping systems [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many scientists have paid great attention to incorporation of allelopathy characteristics into agricultural crop production. The successful use of the technology is expected to significantly reduce dependency on herbicides and effectively protect biodiversity in the ecological environment, thereby dramatically increasing agricultural production and enhancing the quality of products (Mallik 2005;Ni and Zhang 2005;Khanh et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, the reverse side of bioherbicides environmental friendliness (rapid decomposition) is their relative instability in the environment. Thus, it is most appropriate to use natural allelochemicals as the basis for developing new synthetic herbicides, but their chemical structures are often too complicated, and its synthesis at the industrial scale turns out to be extremely expensive [341]. Finally, registration of new products includes very expensive regulatory approval procedures that would not be compensated for by the small profits from the limited use of these pesticides under specific environmental conditions and requirements (for example, in greenhouses or in organic farming) [342].…”
Section: Natural Biopesticides Originated From Treesmentioning
confidence: 99%